Characterization of an A-Type Muscarinic Acetylcholine Receptor and Its Possible Non-neuronal Role in the Oriental Armyworm, Mythimna separata Walker (Lepidoptera: Noctuidae) - Lü, Shumin; Jiang, Ming; Tian, Xing; Hong, Shanwang; Zhang, Junwei; Zhang, Yalin (Frontiers in Physiology, 2020)
Muscarinic acetylcholine receptor (mAChR) regulates many neurophysiological functions in insects. In this report, a full-length cDNA encoding an A-type mAChR was cloned from the oriental armyworm, Mythimna separata. Pharmacological properties studies revealed that nanomolar to micromolar concentrations of carbachol or muscarine induced an increase of intracellular Ca2+ concentration ([Ca2+]i), with the EC50 values of 124.6 nM and 388.1 nM, respectively. The increases of [Ca2+]i can be greatly blocked by the antagonist atropine, with an IC50 value of 0.09 nM. The receptor mRNA is expressed in all developmental stages, with great differential expression between male and female adults. The tissue expression analysis identified novel target tissues for this receptor, including ovaries and Malpighian tubules. The distribution of Ms A-type mAChR protein in the male brain may suggest the neurophysiological roles that are mediated by this receptor. However, the receptor protein was found to be distributed on the membranes of oocytes that are not innervated by neurons at all. These results indicate that Ms A-type mAChR selectively mediates intracellular Ca2+ mobilization. And the high level of receptor protein in the membrane of oocytes may indicate a possible non-neuronal role of A-type mAChR in the reproductive system of M. separata.